A PROBABILISTIC MODEL TO DETERMINE POTENTIAL CARDIOVASCULAR DISEASES GIVEN INDIVIDUAL LIFESTYLES - Amna Shifia Nisafani; Arif Wibisono; Adi Cipta Airlangga (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2017)
Heart diseases introduces a great number of fatalities worldwide. The vast majority of heart diseases are due to unhealthy lifestyle. Unfortunately, these lifestyles are widely unknown until the disease appears. This paper aims at developing a probabilistic model that can help individuals to early detect what type of cardiovascular disease that an individual may have if he/she maintain his/her current lifestyle. We identify factors that cause cardiovascular diseases as well as their intertwined relationships by interviewing cardiovascular experts. Subsequently, we construct Bayesian Network (BN) model based on these factors, and conduct sensitivity analysis. From our study, we obtain 14 lifestyles of cardiac and their relationships. Furthermore, there are 15 nodes of BN model to predicts cardiovascular diseases. In addition, based on our sensitivity analysis, we figure that Congenital Diseases, Type of Exercise, Body Mass Index, and Age are the most important factors contributing to cardiovascular diseases.